GAS6 regulates mucosal langerhans cell homeostasis through cell-intrinsic and niche-dependent mechanisms - Yasmin Jaber; Alon Raviv; Maria Nassar; Nora S. Jaber; Shahd Yacoub; Yasmin Netanely-Rimon; Reem Naamneh; Yaara Tabib; Asaf Wilensky; Avi-Hai Hovav (Proceedings of the National Academy of Sciences, 2026)
Barrier tissues with stratified epithelia rely on Langerhans cells (LCs) to maintain immune surveillance. While TAM signaling regulates skin LC homeostasis, its role in mucosal LC development remains unclear. Here, we identify the TAM ligand GAS6 as a central regulator of oral mucosal LC biology. GAS6 preserves epithelial integrity and restrains local inflammation, while fine-tuning LC abundance by controlling their retention within the tissue. At the precursor level, GAS6 facilitates the proliferation and differentiation of predendritic cells (pre-DCs), particularly pre-DC1. Moreover, GAS6 preferentially supports AXL + pre-DC-derived LCs, without affecting AXL + MERTK + monocyte-derived LCs, leading to a greater contribution of monocytes to the mucosal LC pool. Together, these findings identify GAS6 as a dual-level orchestrator of mucosal LC development and homeostasis.